Structure of a bacterial type IV secretion core complex at subnanometre resolution. (19th March 2013) - Rivera‐Calzada, Angel; Fronzes, Rémi; Savva, Christos G; Chandran, Vidya; Lian, Pei W; Laeremans, Toon; Pardon, Els; Steyaert, Jan; Remaut, Han; Waksman, Gabriel; Orlova, Elena V
<x xml:space="preserve">Abstract</x> Type IV secretion (T4S) systems are able to transport DNAs and/or proteins through the membranes of bacteria. They form large multiprotein complexes consisting of 12 proteins termed VirB1‐11 and VirD4. VirB7, 9 and 10 assemble into a 1.07 MegaDalton membrane‐spanning core complex (CC), around which all other components assemble. This complex is made of two parts, the O‐layer inserted in the outer membrane and the I‐layer inserted in the inner membrane. While the structure of the O‐layer has been solved by X‐ray crystallography, there is no detailed structural information on the I‐layer. Using high‐resolution cryo‐electron microscopy and molecular modelling combined with biochemical approaches, we determined the I‐layer structure and located its various components in the electron density. Our results provide new structural insights on the CC, from which the essential features of T4S system mechanisms can be derived.